Joint channel assignment and routing in multiradio multichannel wireless mesh networks: Design considerations and approaches - Zakaria, Omar M.; Hassan Abdalla Hashim, Aisha; Hassan, Wan H.; Khalifa, Othman Omran; Azram, M.; Jivanadham, Lalitha B.; Sanni, Mistura L.; Zareei, Mahdi (Hindawi Publishing Corporation, 2016)
Multiradio wireless mesh network is a promising architecture that improves the network capacity by exploiting multiple radio channels concurrently. Channel assignment and routing are underlying challenges in multiradio architectures since both determine the traffic distribution over links and channels. The interdependency between channel assignments and routing promotes toward the joint solutions for efficient configurations. This paper presents an in-depth review of the joint approaches of channel assignment and routing in multiradio wireless mesh networks. First, the key design issues, modeling, and approaches are identified and discussed. Second, existing algorithms for joint channel assignment and routing are presented and classified based on the channel assignment types. Furthermore, the set of reconfiguration algorithms to adapt the network traffic dynamics is also discussed. Finally, the paper presents some multiradio practical implementations and test-beds and points out the future research directions.